Surgical treatment of patients with tumours in their distal radius (a review of literature) - Vyrva, Oleg; Burlaka, Victor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article analyzes the scientific literature on the surgical treatment of patients with tumors of the distal radius. Shows the incidence of these lesions and disease entities of the tumor localization. Describes the existing types of tumor resection with an analysis of oncologic outcomes. Analyzed functional results and complications of the different ways the reconstruction of the distal radius after resection of the tumor showing the advantages and disadvantages of each method. An experience of IPPS them. prof. MI Sitenko in the treatment of these patients. Proven benefit and perspectives of joint replacement in the surgical treatment of patients with tumors of the distal radius.